Analisa Model Evaporasi dan Evapotranspirasi Menggunakan Pemodelan Matematika pada Visual Basic di Kabupaten Maros: Analysis of Evaporation and Evapotranspiration Model Using Mathematical Modeling on Visual Basic in Maros Regency - Ahmad Fausan; Budi Indra Setiawan; Chusnul Arif; Satyanto Krido Saptomo (Departemen Teknik Sipil dan Lingkungan, IPB University, 2020)
The approach to calculating evaporation and evapotranspiration, both potential and actual, varies widely. The models used to estimate the amount of evapotranspiration, particularly at the Maros Climatology Station, Maros Regency, South Sulawesi. Evaporation models use the Penman, Priestley, Bruin, and Valiantzas models while evapotranspiration models use the Penman, Hargreaves, Jensen-Haise, Penman-Monteith, Radiation, Turc, and Makkink models, where all of these methods use climate data, such as are the minimum temperature (Tn), maximum temperature (Tx), air temperature (Ta), average humidity (RH), rainfall (R), duration of sun exposure (SS), and maximum wind speed (U) in calculations using Visual basic program in Microsoft Excel in the form of code. Thus, it is necessary to conduct an analysis of the suitability of the model to the results of the observations in order to find out which model is suitable according to the results of the largest coefficient of determination (R2). Based on the results of the model suitability analysis, a selected model was obtained, namely the Valiantzas model with a value of 0.980 in the evaporation calculation and the Jensen-Haise model, namely 0.889.